Do online social interactions cultivate social capital? Evidence from a longitudinal study - Zhou, Dong; Li, Yanan; Tirasawasdichai, Tanin (Frontiers in Psychology, 2022)
It is widely documented that social capital can benefits individual and social development. However, research on the roles of internet technologies in cultivating social capital haven’t achieved a consensus. This article aims to understand the effects of online social interactions (OSIs) on generalized trust and prosocial civic engagement, two essential forms of social capital, with a longitudinal study and structural equation modelling. Fixed-effect model estimations consistently depict that OSIs can effectively increase levels of generalized trust in China. Also, trust in parents is used as an alternative dependent variable to provide a comparative study. Mechanisms of these two sources of trust are different, and insignificant effects of OSIs on trust in parents are found implicitly support the causal link between OSIs and trust in strangers. Moreover, we have implemented a series of robustness checks, for example, examinations using only the netizens sample and cross-sectional methods. Furthermore, we explore the relationship between OSIs and prosocial civic engagement (charitable donation), a behavior form of social capital. SEM results suggest that charitable behaviors are positively affected by OSIs and generalized trust which plays a positive mediating role. Additionally, significant positive direct and indirect effects through generalized trust of OSIs are found on prosocial behaviors.